Knowledge of and Compliance With Guidelines in the Management of Non-Muscle-Invasive Bladder Cancer: A Survey of Chinese Urologists - Wang, Dan-Qi; Huang, Qiao; Huang, Xing; Jin, Ying-Hui; Wang, Yun-Yun; Shi, Yue-Xian; Yan, Si-Yu; Yang, Lu; Li, Bing-Hui; Liu, Tong-Zu; Zeng, Xian-Tao (Frontiers in Oncology, 2021)
Background: Non-muscle-invasive bladder cancer (NMIBC) still poses a heavy load for resulting in many new cases which contribute significantly to medical costs. Although many NMIBC guidelines have been developed, the implementation of them remains deficient. Objective: To analyse Chinese urologists’ knowledge of and compliance with guidelines for NMIBC and identify associated factors. Methods: We conducted an online survey between August 2019 and January 2021. Respondents who were more than 65 years old or did not give the informed consent were excluded. Liner/logistic regressions were performed to identify factors associated with the urologists’ knowledge of and compliance with guidelines, respectively. McNemar’s tests were used to explore the divergence between knowledge and compliance. Results: A total of 814 responses were received. 98.77% of urologists acknowledged the positive effects of high-quality guidelines. The average knowledge score was 6.10±1.28 (out of a full score of 9), and it was positively associated with educational level and the number of guidelines consulted. Only 1.61% and 39.36% of the respondents realized that the guidelines did not recommend further chemotherapy or BCG infusion for low-risk patients. There were 38.87% and 51.84% respondents “often” or more frequently utilizing BCG therapy for intermediate- and high- risk NMIBC patients, respectively. Divergence between knowledge and compliance in performing second TURBT after incomplete initial resection reached statistical significance (p<0.001). Conclusions: Although the vast majority of urologists acknowledged the positive effects of guidelines, knowledge of and compliance with some recommendations of NMIBC guidelines are still inadequate. Factors associated with guidelines, individual professionals, patients, organizations and environment jointly contributed to the non-compliance.